Siza in China – China in Siza. Observations and Reflections on "The Building on the Water". Issue 2 (4th May 2022) - Viana Rodrigues Borges de Araújo, Miguel José
ABSTRACT: The following article contributes to the inscription of Álvaro Siza and Carlos Castanheira's Shihlien office building in China (2010–2014) within Siza's body of work. The Shihlien, also known as the "The Building on the Water, " was an unusual commission for the Portuguese architects, located on a distant site and designed under essentially unknown conditions. The public and critical reception of the building has been shaped by its remote location and private use, as well as by its spectacular form and representation in the media. How, if at all, has China influenced the project and how, reciprocally, has the project influenced China? In analysing Siza and Castanheira's work, the present article re-employs Kenneth Frampton's well-known essays from 1983 on Critical Regionalism and enacts two responses to them: 1) on-site observations of the building, together with a response to the experience of the site in terms of the human senses; 2) critical reflections, supported by photographs and notes, directed back at the Critical Regionalist analysis. In conclusion, I argue that the Shihlien both responds to the local context at the geographical, historical, environmental, cultural levels, and offers a statement of continuity in relation to the rest of Siza's modernist body of works.